Parties' preferences for office and policy goals - Anna Bassi (Games, 2021)
Although parties' preferences for office and policy goals have been featured by many rational choice models of party behavior and a majority of coalition theories, the literature still lacks a measure and a comprehensive analysis of how parties' preferences vary among parties and across countries. This study aims to fill this gap by presenting the results of an original expert survey protocol, which finds that parties pursue both goals simultaneously as office is sought both as and an end and as a means to affect policy, and that the degree to which they prefer policy versus office objectives varies across parties and countries. I provide an application of the preference ratings for policy versus office in the context of government formation, by using the ratings to solve for and predict the equilibrium coalition that should have formed in Spain after the 2015 elections. The government predicted by the model matches the government that formed, providing evidence of the ability of the preference ratings to generate reliable predictions of the composition of government coalitions.
Keywords: 330; expert survey; government coalitions; parties' goals; parties' preferences